Basis for Motion Capture in Terms of Illusory Motion Signal Obtained from Oblique Lines. (August 2014) - Ichikawa, Makoto; Masakura, Yuko
As in the Pinna illusion, when an observer moves their head backwards and forwards while fixating on the center of concentric circles that consist of oblique lines, the observer sees illusory rotation of those circles. When several dots are superimposed on the concentric circles, an observer sees the illusory rotation not only for the circles, but also for those dots (Ichikawa, Masakura, & Munechika, 2006, Perception, 35, 933–946). This illusory rotation of the dots, which have no means of generating illusory motion themselves, is based on motion capture . We examined how the number of dots affects the illusory rotation for such circles and superimposed dots. Results showed that the illusory rotation for the inner circle was most salient when the superimposed dots were extremely numerous or few, although the illusory motion for the dots increased with the increment of the dots. These results suggest that motion capture depends upon a locally obtained motion signal from the oblique lines, and upon the accumulation of the motion signal within the groups of superimposed dots.